New hormones to predict the severity of gallstone-induced acute pancreatitis - Ülger, Burak Veli; Gül, Mesut; Uslukaya, Ömer; Oğuz, Abdullah; Bozdağ, Zübeyir; Yüksel, Hatice; Böyük, Abdullah (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Levels of the hormones ghrelin and leptin in rat models of acute pancreatitis (AP) have been investigated in several experimental studies. However, there are very few clinical studies addressing the connection between hormone levels and AP. A few recent studies investigating the changes in ghrelin and leptin levels in patients with AP have been reported; however, our study is the first clinical study to investigate the change of nesfatin-1 levels in patients with gallstone-induced AP. Materials and Methods: Forty patients were enrolled in this study, eight of which presented with severe AP. Two blood samples were obtained from each study patient. The first blood samples were obtained at patient admission to the hospital and the second was obtained at patient discharge. All samples were collected after at least 6 h of fasting. Plasma nesfatin-1, leptin, and ghrelin levels were measured. Results: In all 40 patients, nesfatin-1 and leptin levels were higher at admission and had decreased at discharge. In contrast, the ghrelin levels at discharge were significantly higher than those at admission. Only the changes in these hormones in the mild AP group were significant. Conclusion: Levels of these hormones were altered during the course of gallstone-induced AP. These changes might be associated with the clinical outcomes of the disease. To clarify whether the magnitude of the change in hormone levels at AP onset can be used as a biomarkers to predict the severity of the disease requires further investigation.